Tryb uproszczony jako docelowy model sprawnego postępowania przed sądami administracyjnymi? - Krzykowski, Przemysław; Hrymowicz, Karolina (PRAWO i WIĘŹ, 2026)
The purpose of this study is to present the arguments that efficient proceedings administrative court proceedings is a simplified procedure. The authors argue that limited evidentiary proceedings before an administrative court and the possibilities offered by the Act on Proceedings before Administrative Courts administrative court proceedings, make it possible to accelerate court proceedings by settling cases in closed sessions.